Enhancing Healthcare Identity and Access Management using Hyper ledger Fabric and OAuth 2.0: A Block chain-Powered Solution for Enhanced Security and Scalability (International Journal of Food and Nutritional Sciences, 2021)
A block chain-driven framework for managing identity and access emerges as a promising remedy to the privacy and security concerns in sharing patient data within the healthcare sector. This innovative technology guarantees the safeguarding of sensitive information's confidentiality and integrity by establishing a decentralized and immutable ledger. Our study introduces an identity and access management system leveraging the capabilities of Hyperledger Fabric and OAuth 2.0, thereby augmenting security and scalability. The amalgamation of these technologies ensures the transparency and immutability of user transactions, substantially mitigating the risks of fraudulent activities and unauthorized entries.Furthermore, Hyperledger Fabric's prowess in privacy, security, and scalability empowers the implementation of meticulous access control mechanisms for sensitive data. Simultaneously, OAuth 2.0 validates solely trustworthy third-party applications' access to specific data within the Fabric network. This novel approach seamlessly handles voluminous data loads and supports diverse applications, thus constituting a secure and scalable solution for administering access within the Fabric network. In addition to these attributes, our solution incorporates a Role-based Access Control model, aligning access privileges with a patient's designated role to uphold their privacy and confidentiality. Our rigorous statistical analysis validates the effectiveness and security of the proposed strategy in competently managing patient identity and access. Furthermore, the proposed solution seamlessly aids compliance with regulatory mandates like HIPAA and GDPR.